2009
DOI: 10.1002/hipo.20643
|View full text |Cite
|
Sign up to set email alerts
|

Fornix transection selectively impairs fast learning of conditional visuospatial discriminations

Abstract: As the fornix has previously been implicated in the rapid learning of associations, we hypothesized that fornix transection in macaques would selectively impair the acquisition of rapidly learned conditional visuospatial discrimination problems. Macaque monkeys learned, postoperatively, three sets of concurrent problems of increasing sizes containing 8, 32, and 64 problems, respectively. Each problem consisted of four identical visual stimuli and animals had to learn which stimulus position was rewarded. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Previous work has shown the importance of the fornix for memory function (Aggleton, 2008; Tsivilis et al , 2008). In humans, damage to the fornices produces memory deficits (Gaffan and Gaffan, 1991; McMackin et al , 1995; Park et al , 2000; Kesler et al , 2001) and, in the monkey, the fornix has been shown to be critical for the rapid learning of new spatial and non-spatial associations (Brasted et al , 2002, 2003; Kwok and Buckley, 2010). Following traumatic brain injury, the extent of damage to the hippocampi is known to predict memory impairment (Tate and Bigler, 2000), and mean diffusivity within the hippocampal formation has been shown to predict associative memory function (Salmond et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown the importance of the fornix for memory function (Aggleton, 2008; Tsivilis et al , 2008). In humans, damage to the fornices produces memory deficits (Gaffan and Gaffan, 1991; McMackin et al , 1995; Park et al , 2000; Kesler et al , 2001) and, in the monkey, the fornix has been shown to be critical for the rapid learning of new spatial and non-spatial associations (Brasted et al , 2002, 2003; Kwok and Buckley, 2010). Following traumatic brain injury, the extent of damage to the hippocampi is known to predict memory impairment (Tate and Bigler, 2000), and mean diffusivity within the hippocampal formation has been shown to predict associative memory function (Salmond et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies of fornix transection have shown deficits in spatial cognition, particularly in the rapid acquisition of spatial relationships [39,40]. DTI measures in the fornix can also discriminate between healthy controls and patients with AD and MCI [34,41].…”
Section: Discussionmentioning
confidence: 99%
“…These hub SNPs influenced intellectual performance by modulating the associations between performance IQ and the integrity of the fiber systems that are part of visuospatial circuits (Chiang et al, 2009b; Kravitz et al, 2011), including the optic radiations (Tuch et al, 2005), fornix (Kwok and Buckley, 2010), corpus callosum (Begre et al, 2007), cingulum bundle (Bush et al, 2000), and the superior longitudinal fasciculus, which is associated with spatial working memory performance in children (Vestergaard et al, 2011). Human intelligence is highly heritable; a substantial proportion (40–50%) of variation in IQ is genetically determined (Davies et al, 2011).…”
Section: Discussionmentioning
confidence: 99%